SOME ASPECTS OF THE PREVENTION AND REHABILITATION OF CARDIAC PATIENTS - Rustam U. Aibazov (Вестник Северо-Кавказского федерального университета, 2022)
The article presents data on the role of physical activity in the rehabilitation of cardiological patients. It examined the role of informing patients of a physician and co-decision on the choice of tactics of treatment of the disease.